Factors influencing learning in MOOCs (Massive Open Online Courses) - Holanda, Ana Carla A.; Tedesco, Patrícia C. A. R. (Anais do Workshop on Advanced Virtual Environments and Education (WAVE); 2019: Anais do II Workshop on Advanced Virtual Environments and Education, 2019)
Massive Open Online Courses (MOOCs) are remote courses that stand out in heterogeneity and quantity of their students. Due to the peculiarity of being massive and the large amount of data generated, it is necessary to identify which factors influence the learning process based on collaboration. Thus, the objective of the research was to identify the variables that can promote autonomous and critical learning. The results of a Systematic Literature Mapping have brought us important evidence in the process of developing a collaborative framework in MOOCs.